SOCIO-LEGAL CHALLENGES OF INDIGENOUS LAND IN WEST KALIMANTAN: CUSTOMARY PRACTICES AND NATIONAL LAW - Kurniawan, Itok Dwi; Aldyan, Arsyad; Septiningsih, Ismawati; Rustamaji, Muhammad; Santoso, Bambang; Santos, Jose Gama (Jurnal Pembaharuan Hukum, 2024)
Customary law in the national legal system is undoubtedly fundamental to maintaining existence because customary law can also be applied to resolve conflicts in society. This research uses socio-legal methods, and the data obtained is based on data in the field through an interview process with several related parties. In contrast, for legal problems in this society, only some things can be resolved through a customary law approach. For example, in the Dayak indigenous community, several legal problems cannot be resolved according to custom, especially regarding unregistered land rights. These problems certainly cannot be solely resolved using a customary law approach. This certainly shows that customary law cannot necessarily accommodate the interests of Indigenous peoples because this is also closely related to legal certainty. Because they relate to legal certainty, they must be resolved through a positive legal approach, such as submitting a request to the court or an application to the relevant agency. This certainly happens because the legal awareness of regional communities in Indonesia is currently not very good; this leads to legal issues within indigenous communities that cannot be resolved through customary law.